(3GdNHQ GdGPGYj (B:s (3afhfg hNUGFUg aj GdQGOjh h GdJdaRjhf (B/s - (3TdHj, cQe s ((3LOI (B:s (3OGQ GdTQhb ,s, 1985)
(3SjLO GdbGQF aj gPG GdHMK GdcKjQ Yf afhf GdYed GdGNHGQj aj GdQGOjh h GdJdaRjhf HOGjI ef JYQja GdNHQ h cjajI GdMUhd Ydjg (B..(3Gdi cjajI GYOGO GdGNHGQ h JbOjegG aj GTcGdgG GdeNJdaIs
Keywords: (3GdGPGYj s; (3GdNHQs; (3NUGFU s; (3afhf s